The Protein Corona as a Confounding Variable of Nanoparticle-Mediated Targeted Vaccine Delivery - Bros, Matthias; Nuhn, Lutz; Simon, Johanna; Moll, Lorna; Mailänder, Volker; Landfester, Katharina; Grabbe, Stephan (Frontiers in Immunology, 2018)
Nanocarrier (NC) are a very promising for cancer immunotherapy. Whereas conventional vaccines are based on the administration of an antigen and an adjuvant in an independent fashion, nanovaccines can facilitate cell-specific co-delivery of antigen and adjuvant. Furthermore, nanovaccines can be decorated on their surface with molecules that facilitate target-specific antigen delivery to certain antigen-presenting cell types or tumors. However, the target cell-specific uptake of nanovaccines is highly dependent on the modifications of the nanocarrier itself. One of these is the formation of a protein corona around NC after in vivo administration, which may potently affect cell-specific targeting and uptake of the NC. Understanding the formation and composition of the protein corona is therefore of major importance for the use of nanocarrier in vaccine approaches. This Mini Review will give a short overview of potential non-specific interactions of NC with body fluids or cell surfaces that need to be considered for the design of NC vaccines for immunotherapy of cancer.